2015
DOI: 10.11606/rai.v12i1.100324
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Indutores À Inovação Tecnológica Da Indústria Madeireira Da Região De Lages/Sc

Abstract: RESUMOObjetivou-se analisar as variáveis que interferem na adoção de inovações tecnológicas de empresas madeireiras da região de Lages/SC, suas características e a conduta padrão das firmas quanto à inovação. A pesquisa contemplou 36 empresas e os dados foram coletados via questionário e submetidos à análise de regressão logística (logit) e à Principal Component Analysis (PCA). Os resultados indicam que a inovação está associada à localização em um ambiente externo mais competitivo, ao aumento do tempo de vida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Technological innovation in the timber industry has prominence in the business environment, providing greater efficiency in the use of raw materials, mitigation of environmental impacts and sectorial competitiveness (Simioni et al 2015). In the region of Lages, Santa Catarina, Brazil, these issues are important, since forest-based industry constitutes a production complex that uses planted forests to produce pulp and paper, solid wood and energy (Simioni and Hoeflich 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological innovation in the timber industry has prominence in the business environment, providing greater efficiency in the use of raw materials, mitigation of environmental impacts and sectorial competitiveness (Simioni et al 2015). In the region of Lages, Santa Catarina, Brazil, these issues are important, since forest-based industry constitutes a production complex that uses planted forests to produce pulp and paper, solid wood and energy (Simioni and Hoeflich 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the availability of forest biomass, a power cogeneration plant was installed in 2004 (Engie Brazil Energy), for the production of thermal and electrical energy (Hoff and Simioni 2004;Simioni et al 2012). A decade after the implementation of the cogeneration unit in Lages, Simioni et al (2015) showed that there were significant changes in the quality of biomass and in the efficiency of the energy production process, which are associated with the applications of technological innovations.…”
Section: Introductionmentioning
confidence: 99%